(untitled) (Revista Electrónica Calidad en la Educación Superior, 2025)
The objective of this article is to describe the design of a diagnostic test of prior mathematics knowledge required for calculus courses. The test was administered to 2,634 people and presented a factorial structure of three factors: algebra, functions and specific knowledge of post-secondary mathematics, whose Cronbach’s alphas were .88, .83 and .66, respectively. The results in all sections were very low (75th percentile less than 5, on a scale of 0 to 10). In particular, the lowest scores obtained belong to the postsecondary knowledge section and algebra. We expect these results will be of practical use in designing policies aimed to population examined.